Ultraviolet Radiation – Level of Knowledge and Health Protection of College Students in Slovakia. An Educational-Questionnaire Study - Viera Jakusova; Klara Capova; Ivan Poliacek; Ivo Cap; Jan Jakus (Communications - Scientific letters of the University of Zilina, 2012)
It is generally acknowledged that there is a correlation between the incidence of ultraviolet burden diseases and overexposure of the body to ultraviolet radiation (UVR). The main goals of our study were to determine the level of knowledge of college students in regard to the effects of UVR, to educate them about it, and finally to urge them to improve their personal protection against the harmful effects of UVR. We performed an educational-questionnaire study of UVR in 2003, 2005, and 2008 years. Responses of 841 students from Jessenius Faculty of Medicine in Martin (JFM), University of Zilina, and St. Elizabeth College of Health and Social Work (SEC) in Bratislava showed a higher level of knowledge in students at JFM and Univ. of Zilina following their education, as compared to those students from SEC. There was little difference in responses to questions related to the protection against UVR. A lower level of knowledge in all groups of students was shown in 2005. Nevertheless, all respondents significantly increased their level of protection against UVR during the years of the study and the number of those visiting solaria decreased. A weak relationship between the knowledge of students and their protection skills against UVR was found, indicating that a complex reason might be involved. This study highlights the importance of providing education that is systematic and longterm to university students in Slovakia (future doctors, bioengineers and nurses). Moreover, this study brings new insights on the surveillance and protection against the harmful effects of UVR to prospective patients.